VALENTINE DAY TIDAK HARUS MENUJU PERZINAHAN - Prasiska, Gadis; Theo, Ivana; Adiputra, Jahya; Yunita, Sri (Inspiratif Pendidikan, 2023)
Valentine's Day or what is known as Valentine's Day is very popular among young people and is the most eagerly awaited moment on February 14th. Valentine's Day is often celebrated every year so that it becomes a culture and a trend. Valentine's Day is synonymous with flowers, chocolates, dolls, and some people even celebrate this day with sex parties. This culture is practiced by young people from various countries and including Indonesia, which increasingly refers to the damage to Indonesian culture and morals. Therefore this research was carried out to make people aware of deviations from Valentine's Day and the negative impact on Indonesian culture and provide enlightenment from the aspects of religion, society, government and in the eyes of education. In analyzing this case the writer uses descriptive qualitative research methods. The results of this study regarding the thoughts and views of cultural agencies regarding acts of deviation from Valentine's Day celebrations.